Defining the climate for inclusiveness and multiculturalism: Linking to context - J. Barton Cunningham (Administrative Sciences, 2023)
The purpose of this paper is to develop a better understanding of how to define a positive climate for inclusiveness that recognizes the context and social environment of participants. In order to study employees working with Indigenous people and minorities in four organizations, we used a grounded research approach to define what an inclusive environment might look like. The interview questions gathered examples of experiences which employees valued because they felt more included and not excluded from people they worked with. The experiences fell into four categories, as follows: (i) leadership engaged in supporting inclusiveness within the organization; (ii) leadership engaged in seeking inclusiveness within the community; (iii) being involved in multicultural practices within the organization and community; and (iv) participating in initiatives which encourage engagement and involvement. This paper's conceptualization of a climate of inclusion is different from other studies, possibly because of the unique context in which service organizations are placed, as such organizations typically work with Indigenous people and minorities. Although we are especially mindful of the danger of generalizing our findings without further research, the scope of this paper might provide some direction for future studies of other organizations. We suggest that there is also a need to be open to methods which allow individuals and groups to define a climate of inclusivity that is relevant to their context; this is because context may be essential for recognizing certain groups of people.
Keywords: 350; context; diversity; inclusion; multiculturalism